Montado’s Ecosystem Services - Batista, Teresa (2017)
Although the concept of ecosystem services is well defined and centred on human use of natural systems, it is not yet consensual. The ecosystem services connect ecology and economy; they allow to integrate ecology into policies and to bring a monetary value. Even if the authors do not entirely agree with the idea of giving a monetary value to all elements, living and not living, they consider that the concept of ecosystem services can be improved in the sense of a holistic landscape ecological approach. Montado is a high valuated cultural landscape typical from the Southwest of Iberian Peninsula. It concerns a human-shaped ecosystem composed by a mosaic of scattered cork oaks, holm oaks or mix oaks, with a high grazing diversity. The most important products of Montado are cork and other non-timber products. Nevertheless its highly value is on the ecosystem functions it can provide, namely water cycle regulation, carbon sequestration and conservation of biodiversity, soil and cultural landscape values. These ecosystem services are highly interconnected, and have a lot of dependences in a complex structure. So, the first goal of this paper is to identify the main Montado ecosystem services that must be valued in sustainable management and policies, in order to prevent biodiversity losses and other types of ecosystem and landscape degradation. It is therefore of the utmost importance enhance Montados ecosystems services knowledge.